웹-기반 Tangible Space - 고희동; 서대일; 유병현 ((사)한국컴퓨터그래픽스학회, 2017)
Tangible Space is a new emerging interaction space with mobile AR/VR computing and ubiquitous computing environment with IoT. Tangible Space spans from a physical environment augmented with virtual entities to immersive virtual environments mirroring the physical environment. Interacting with Tangible Space is logged just like interacting with the Web. By webizing Tangible Space, we can gain persistence as a by-product so that human life experience in the physical environment can be logged and shared just like the information being created and shared in the current Web. The result is a powerful future direction of the web from a World Wide Web of Information to World Wide Web of Life experiences.